Hidrolisis Hemiselulosa Batang jagung Dengan Proses Organosolv menggunakan Pelarut Asam Formiat - Desi Ivo Andri Ari; Zuchra Helwani; Zulfansyah Zulfansyah; Hari Rionaldo (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Corn stalk is solid waste of agricultural which is not optimally utilized. Corn stalk used for pulp and paper raw materials and also used for feeding animal. The aim of hemicellulose hydrolysis from corn stalk is to study the possibility of utilization corn stalks as raw material for chemical industry, to know the behaviour and to obtain the kinetics pattern of hemicellulose hydrolysis from corn stalk in organosolv process. The experimental of hemicellulose hydrolysis from corn stalk is carried out in a batch at laboratory scale. Experimental variables are, concentration of formic acid (70; 80; 90% wt), the reaction time (0, 15, 30, 45, 60, 75, 90,105, 120, 135, 150, 165, 180 minutes) and ratio of liquid-solid is 10:1, with catalyst hydrochloric acid 0.2% wt. The experimental result shows that the hydrolysis of hemicellulose from corn stalk in organosolv process produce xylose and furfural which can be used as raw material in industry. Diluted xylose and furfural in black liquor in this experiment are xylose (0.88-3,78 gr/liter) and furfural (1.7-3.69 gr) with percentage of hemicellulose recovery range from 37-82%. The behaviour of hemicellulose hydrolysis from corn stalk in media formic acid show two series processes that have a different rate. Experimental conformity data exceeded 95% (R-square 95%) with the model hydrolysis of hemicellulose that proposed by Parajo et al [1993]. Key words: formic acid, hydrolysis of hemicellulose, corn stalk, organosolv